Managment and construction of water front: between the public action and the private iniciative. Playa de los Ingleses, 1945-1970 - Savino, Mariano (Universidad Nacional de Mar del Plata. Facultad de Arquitectura, Urbanismo y Diseño, 2007)
This work analizes the management and construction`s process of water front: In particular, a section called Playa de los Ingleses, renamed Varese, in Mar del Plata city, between 1945 and 1970.It`s part of a proyect in which the central hipothesis afirms that this section development was slower than other central sections, due to the absence of state`s totalizing interventions.New mecanisms of private management start during this period, it began with the Ley de Propiedad Horizontal in 1948, and from then on, a new way of building the water front changed it radically. In this way, we studie four blocks which began to get built during this period and in this context making a different urban landscape.